Intact rock bridge breakage and rock mass fragmentation upon failure: quantification using remote sensing techniques. (14th December 2017) - Spreafico, Margherita C.; Franci, Francesca; Bitelli, Gabriele; Borgatti, Lisa; Ghirotti, Monica
Abstract: In this work, two processes related to the onset and the evolution of large‐scale rockfalls have been analysed by means of remote sensing techniques. First, the number of rock bridges as a proportion of pre‐existing fractures has been estimated in a newly formed landslide scarp by analysing the spectral information of the rock mass in terrestrial laser scanner (TLS) and unmanned aerial vehicle (UAV) photogrammetric point clouds. Second, the fragmentation of the rock mass after failure has been assessed by comparing the percentage of newly formed fractures in the scarp and in the deposit. For this purpose, an orthophoto of the landslide deposit was classified using an object‐based method. The presented workflow gained new data on the intact rock breakage during and after failure, and consequently deepened knowledge about rock failure and fragmentation mechanisms.